2008
DOI: 10.5194/acp-8-921-2008
|View full text |Cite
|
Sign up to set email alerts
|

Lightning activity in Brazilian thunderstorms during TROCCINOX: implications for NO<sub>x</sub> production

Abstract: Abstract. During the TROCCINOX field experiment in January and February 2005, the contribution of lightninginduced nitrogen oxides (LNOx) from tropical and subtropical thunderstorms in Southern Brazil was investigated. Airborne trace gas measurements (NO, NO y , CO and O 3 ) were performed up to 12.5 km with the German research aircraft Falcon. During anvil penetrations in selected tropical and subtropical thunderstorms of 4 and 18 February, NO x mixing ratios were on average enhanced by 0.7-1.2 and 0.2-0.8 nm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 92 publications
4
62
0
Order By: Relevance
“…Unlike the Brazilian (Huntrieser et al, 2008) and Australian (Huntrieser et al, 2009) thunderstorms, the AMMA MCSs showed a greater influence from boundary layer versus lightning NO x . The tropical and subtropical MCSs investigated during AMMA indicated LNO x production rates (70 moles flash −1 and 179 moles flash −1 , respectively) were comparable to those observed in similar air mass thunderstorms during TROCCINOX.…”
Section: Lno X Production In Tropical Thunderstormsmentioning
confidence: 74%
See 2 more Smart Citations
“…Unlike the Brazilian (Huntrieser et al, 2008) and Australian (Huntrieser et al, 2009) thunderstorms, the AMMA MCSs showed a greater influence from boundary layer versus lightning NO x . The tropical and subtropical MCSs investigated during AMMA indicated LNO x production rates (70 moles flash −1 and 179 moles flash −1 , respectively) were comparable to those observed in similar air mass thunderstorms during TROCCINOX.…”
Section: Lno X Production In Tropical Thunderstormsmentioning
confidence: 74%
“…Observed lightning data and a LNO x vertical distribution (Pickering et al, 1998) were used in conjunction with aircraft NO x observations to estimate LNO x production rates of 31-73 moles flash −1 for one storm and 348-813 moles flash −1 in a second system. Based on the Tropical Convection, Cirrus, and Nitrogen Oxides Experiment (TROCCINOX) in Brazil, the LNO x mass production for tropical thunderstorms was of similar magnitude as that found for one of the BIBLE-C storms (∼ 70 moles flash −1 ), while a subtropical thunderstorm also analyzed during the campaign had a production rate of ∼ 140-210 moles flash −1 (Huntrieser et al, 2008). Huntrieser et al (2009) (Labrador et al, 2009), while later in the ACTIVE experiment (e.g., January 2006) enhancements in LNO x were found over widespread regions.…”
Section: Lno X Production In Tropical Thunderstormsmentioning
confidence: 78%
See 1 more Smart Citation
“…Since both, WWLLN DE and PE, increase almost linearly with peak current, we probably can not explain the category C events by less productive flashes due to low peak currents. Huntrieser et al (2008) report on relatively low PE for tropical thunderstorms during the TROCCINOX campaign in Brazil, in contrast to subtropical thunderstorms, and could relate this to a difference in average stroke lengths. They propose that tropical thunderstorms have generally shorter flash lengths, and are thus generally less productive with respect to LNO x /flash, than subtropical thunderstorms, as a consequence of enhanced vertical wind shear of the latter.…”
Section: Factors Determining Pementioning
confidence: 92%
“…The dimensions of a SCIAMACHY ground pixel are 30 × 60 km 2 . This dimension corresponds approximately to a time interval of 1 h, as wind speeds in the upper troposphere are of the order of 10-20 m/s (compare Huntrieser et al, 2008, Table 4c therein). We thus consider flashes for 1 h back in time.…”
Section: Relation Of No 2 Tscd and Wwlln Frdmentioning
confidence: 99%